Use of proton pump inhibitors and the risk of coronary events in new users of low-dose acetylsalicylic acid in UK primary care - Rodríguez, Luis A. García; Johansson, Saga; Nagy, Péter; Soriano, Lucía Cea (Thrombosis and Haemostasis, 2014)
This study evaluated the risk of cardiovascular events associated with the use of proton pump inhibitors (PPIs) in new users of acetylsalicylic acid (ASA) for the secondary prevention of cardiovascular events. Two cohorts of patients aged 50–84 years were identified from UK primary care databases: individuals with a first prescription for ASA (75−300 mg/day) for secondary prevention of cardiovascular events (n = 39,513; CVD cohort) or with a record of hospitalisation for an acute coronary event (n = 42,542; ACS cohort) in 2000–2007. Cases of nonfatal myocardial infarction (MI) and coronary death were identified: 1,222 in the CVD cohort and 604 among new users of ASA in the ACS cohort. A nested case–control analysis estimated the relative risk (RR) of non-fatal MI or coronary death associated with use vs non-use of PPI therapy. Current continuous use of PPI therapy was not associated with a significant increase in RR overall: in the CVD cohort (RR = 1.14 [95% confidence interval = 0.91−1.43]); in the ACS cohort (0.88 [0.66−1.18]); or among current continuous users of ASA as antiplatelet monotherapy (CVD cohort: 1.15 [0.80−1.66]; ACS cohort: 0.73 [0.43−1.23]; pooled analysis of both cohorts: 0.96 [0.62−1.48]). In conclusion, among first-time users of ASA for the secondary prevention of cardiovascular events, PPI use was not shown to be associated with an increased risk of non-fatal MI or coronary death.
Keywords: Acetylsalicylic acid; aspirin; proton pump inhibitors; myocardial infarction; cardiovascular